Situation Report: Romania, 10 June 1966 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Chou Visit Announced Ceausescu Touring Arges Region New First Secretary of Bucharest Appointed Romanian Premier to Visit Denmark Romania Attacks US at Labor Conference Ceausescu Receives Delegations Mongolian Party Congress Revival of the Thriller in Romania Miscellaneous